MANUSIA DAN KEBUDAYAAN DALAM PERSPEKTIF PENDIDIKAN TRANSFORMATIF: DARI PEWARISAN MENUJU PENCIPTAAN NILAI BARU - Shinta Anugrah Ikhtiarini; Prof. Dr. Wasino, M.Hum.; Argitha Aricindy Ph.D (STKIP Subang, 2025)
Transformative education views humans as active subjects in the process of cultural formation and renewal. Education is no longer merely a means of transmitting static cultural values, but a vehicle for developing critical awareness and creativity in creating new values relevant to the progress of the times. This study aims to analyze how transformative education can shift the paradigm of passive cultural inheritance into a creative process of new cultural creation. The method used is a qualitative-descriptive approach with literature analysis based on Paulo Freire’s theory of liberating education. The results show that transformative education plays a vital role in fostering reflective ability, critical thinking, and social awareness among learners to re-evaluate existing cultural values and reconstruct them according to the needs of contemporary society. Education encourages the creation of a balance between the preservation of local culture and modern innovation. In conclusion, transformative education serves as an essential medium for shaping individuals not only as inheritors but also as creators of new culture that is adaptive, inclusive, and rooted in human values.